Influence of root canal instrumentation file systems and obturating materials on the success of pulpectomized teeth: A secondary analysis from a randomized controlled trial - Girish Babu KL; Kavyashree Gururaj Hebbar (Arbu Academic Publishing, 2024)
Aim: This study aimed determine the influence of the type of root canal instrumentation file systems and obturating materials on the success of pulpectomized teeth. Methods: Two hundred eighty-eight primary molars from children aged 4-7 years were selected and divided into three groups of 96 teeth each. In the first, second, and third groups, root canal instrumentation was performed using Kedo-SG pediatric rotary files (KS), HERO Shaper rotary files (HS), and manual Ni-Ti K-files (MF), respectively. Following instrumentation, these three groups were subdivided into three subgroups of 32 teeth each and obturated using zinc oxide eugenol, Endoflas®, and DiaPex Plus®. The quality of the root filling was assessed immediately and evaluated clinically and radiographically over two years. The Chi-Square Test was used to analyze the data, with the level of significance set at P<0.05. Results: The quality of obturation was superior in root canals instrumented with rotary file systems compared to manual files. No significant difference in obturation quality was noted among the obturating materials used. The clinical success rate after two years was 100%. Radiologically, success rates were 97% for Kedo-SG, 94% for HERO Shaper, and 89% for manual file systems. For obturating materials, the success rates were 90%, 96%, and 94% for zinc oxide eugenol, Endoflas®, and DiaPex Plus®, respectively. Conclusions: The success of pulpectomized teeth was not significantly influenced by the type of root canal instrumentation file systems or the choice of obturating materials.